Investigating the Link Between Knowledge and Earthquake Preparedness among High School Students - Rahmawati, Nanda Eka; Wibowo, Yunus Aris; Widiyatmoko, Wahyu (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to determine students' knowledge of earthquake disasters, assess students preparedness in facing earthquake disasters, and analyze the relationship between knowledge and preparedness among students of SMA Negeri 1 Wedi.Methodology: The study was conducted at SMA Negeri 1 Wedi with a population of 745 students. A sample of 260 students was selected using the Slovin formula with a 5% margin of error. Data were collected through tests, questionnaires, and documentation. The sampling technique used was Stratified Random Sampling, and data analysis was performed using the Product Moment correlation test.Results: The results indicate that most students fall into the moderate knowledge category, suggesting that their understanding of earthquake disaster still needs improvement. Students with low knowledge account for 13%, while only 10% demonstrate high knowledge, highlighting the need for more intensive disaster education. In terms of preparedness, students are also predominantly the moderate category, indicating basic but not optimal preparedness. Only 3% of students show high preparedness, while 10% remain at a low level. Correlation analysis show a significant relationship between knowledge and disaster preparedness, with a Sig. (2-tailed) value of 0.000 <0.05, confirming that higher knowledge levels are associated with better preperedness.Applications/Originality/Value: The findings emphasize the importance of strengthening disaster education to improve both students' knowledge and preparedness. Schools are encouraged to integrate earthquake disaster education into the curriculum and conduct regular training and simulations to optimize students' readiness in facing potential disasters.